2018
DOI: 10.1242/jcs.208215
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of the plant ERF transcription factors in coordinating wound defense responses and repair

Abstract: Plants react to wounding through the activation of both defense and repair pathways, but how these two responses are coordinated is unclear. Here, we put forward the hypothesis that diverse members of the subfamily X of the plant-specific ethylene response factor (ERF) transcription factors coordinate stress signaling with the activation of wound repair mechanisms. Moreover, we highlight the observation that tissue repair is strongly boosted through the formation of a heterodimeric protein complex that compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 107 publications
2
70
0
Order By: Relevance
“…We also found other ethylene signaling genes with significantly altered expression at day 9 (T = 3), including a predicted ethylene dependent gravitopismdeficient like gene (Cc02_g06740; FC = −3.13), multiple ethylene-responsive transcription factors (Cc05_g07590, FC = 2.21; Cc02_g03420, FC = 6.98; and Cc06_g12520, FC = 2.96), and two AP2 related TF genes (Cc10_g07680; FC = −3.09 and Cc08_g15690, FC = −3.13). Transcript changes for some ethylene related TFs could be due to overlaps between wound/damage-related responses and drought related responses (Heyman et al 2018). This is supported by the observation that several defense related genes also showed transcriptional changes at the higher water deficit, including putative disease resistance proteins (Cc01_g02600, FC = −5.16 and Cc02_g26510, F = 3.95) and pathogen related proteins (Cc11_g07780, FC = 4.68 and Cc10_g14270, FC = 4.3).…”
Section: Discussionmentioning
confidence: 99%
“…We also found other ethylene signaling genes with significantly altered expression at day 9 (T = 3), including a predicted ethylene dependent gravitopismdeficient like gene (Cc02_g06740; FC = −3.13), multiple ethylene-responsive transcription factors (Cc05_g07590, FC = 2.21; Cc02_g03420, FC = 6.98; and Cc06_g12520, FC = 2.96), and two AP2 related TF genes (Cc10_g07680; FC = −3.09 and Cc08_g15690, FC = −3.13). Transcript changes for some ethylene related TFs could be due to overlaps between wound/damage-related responses and drought related responses (Heyman et al 2018). This is supported by the observation that several defense related genes also showed transcriptional changes at the higher water deficit, including putative disease resistance proteins (Cc01_g02600, FC = −5.16 and Cc02_g26510, F = 3.95) and pathogen related proteins (Cc11_g07780, FC = 4.68 and Cc10_g14270, FC = 4.3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ET biosynthesis genes, many APETALA2/ETHYLENE RESPONSE FACTOR ( AP2/ERF ) genes were differentially expressed at various stages during the process. Several AP2/ERF genes have been recently identified as potent players in regulation of tissue repair, de novo organogenesis and regeneration (Heyman et al ), indicating possible roles of the ET‐induced AP2/ERF genes in AR formation.…”
Section: Ethylene: the Gas That Mattersmentioning
confidence: 99%
“…Our results suggested that the wild alleles of ScWRKY023 and ScWRKY045 might represent promising candidates for multiple stress responses as they are leaf-specific and constantly expressed after wounding in S. commersonii but not in the cultivated potato. In addition, WRKY023 is also induced by bacterial infection and it is suggested to interact with both a WRAF2-like protein and with the LRR mediated immunity system 74,75 .…”
Section: Identification Of Tissue-specific and Stress Responsive Wrkymentioning
confidence: 99%